IMPLEMENTATION OF FULL DAY SCHOOL IN FORMING MORALS IN PRIMARY SCHOOL STUDENTS AT TAHFIDZ PLUS SCHOOL KHOIRU UMMAH HIGH CLIFF - M. Alang Khairun Nizar (RADJA PUBLIKA, 2024)
This research aims to find out how the implementation of Full Day School shapes the morals of elementary school students at the Tahfidz Plus Khoiru Ummah Tebing Tinggi School. By conducting this research, it is hoped that it will increase knowledge and provide benefits for those involved in shaping the morals of elementary school students at the Tahfidz Plus Khoiru Ummah Tebing Tinggi School, where this research was conducted. This type of research is descriptive qualitative research, and the data collection tools are in the form of observation, interviews and documentation. Data analysis is carried out by giving meaning to the data obtained and then drawing conclusions. From the data collection process and data analysis carried out, results were obtained in the form of: the implementation of the full day school system can provide positive results. It can be seen from the students' religious behavior that there have been several changes through the implementation of the full day school system with learning implemented at the Tahfidz Plus Khoiru Ummah Tebing Tinggi School, such as the habit of praying in congregation, memorizing the Koran, and minimizing negative student behavior outside of school.